From oral tradition to digital preservation: A systematic review of efforts to sustain local literatures in the Modern era - Alvons Habibie; Harto S. Malik (LP2M IAIN Sultan Amai Gorontalo, 2026)
Background: The preservation of local literature rooted in oral traditions faces new challenges and opportunities in the digital era. Digital technologies enable documentation and wider dissemination, yet they also raise concerns about cultural authenticity, community sovereignty, and sustainability. A systematic synthesis is required to clarify current scholarly directions. Aims: This study aims to: (1) identify dominant themes and research approaches in recent studies on the digital preservation of local literatures; (2) examine how scholars conceptualize the shift from oral to digital forms; and (3) analyze the documented educational impact of digitization within indigenous and local communities. Methods: A Systematic Literature Review (SLR) was conducted following PRISMA 2020 guidelines. Searches across Scopus, Google Scholar, EBSCOhost, and ProQuest covered English and Indonesian publications from 2010–2025. Studies focused on preserving local literary content were included, while purely technical works were excluded. Data were synthesized through thematic analysis. Results: Six thematic clusters emerged: Digital Tools and Innovation; Community Participation and Co-Creation; Ethical Access and Cultural Protocols; Multimedia Storytelling; Digital Knowledge Management; and Collaborative Institutional Models. Scholars largely frame digital transition as cultural continuity and narrative hybridity shaped by technology but grounded in community stewardship and digital sovereignty. Educationally, digitization enhances reading comprehension, writing skills, engagement, accessibility, and cultural relevance. Implications: Effective preservation requires culturally grounded, participatory, and multidisciplinary approaches. Policymakers and practitioners should strengthen community-led digital stewardship, establish ethical access guidelines, and integrate digitized local literatures into curricula for sustainable cultural continuity.